Studi Meta Analisis: Pengaruh Media Pembelajaran Berbasis Video Sebeum dan pada Waktu Pandemi Covid 19 - Rafiqurrahman, Muhammad Rois; Suryaningtyas, Wahyuni; Soemantri, Sandha (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of video-based learning media before and during the pandemic. The method used is the systematic literature review method by reviewing and analyzing 6 articles related to the influence of video-based learning media before the pandemic and 6 articles during the pandemic on mathematics learning. The results of the meta-analysis using the effect size show that the influence of pre-pandemic video-based learning media has an influence on trigonometry material, flat sided geometric material, social arithmetic material, set material, and circle material and also has an influence on the dependent variable problem solving ability, understanding of mathematical concepts, learning outcomes, and creative thinking skills. The effect of video-based learning media during a pandemic had an influence on SPLDV material, number pattern material, statistics material, transformation material, straight line equation material and circle material and also had an influence on the dependent variable of learning outcomes, understanding of mathematical concepts, problem solving abilities. In conclusion, the effect of video-based learning media during a pandemic has an average effect size that is larger than the influence of video-based learning media before the pandemic. Keywords: Learning media, Learning videos.